Gestos didáticos em salas heterogêneas. - Cottica, Angela Maria (2013)
This research aims to describe, categorize and evaluate in terms of relative effectiveness inclusive teaching gestures, which are understood as discursive action units that enable a more effective interaction between teachers and students. The corpus of this study consisted of transcripts of scenes filmed lessons and / or observations in loco in classes of the 6th and the 7th grades of primary education in state schools, located in the municipalities of Entre Rios do Oeste and Marechal Cândido Rondon. Scenes of thirteen lessons were transcribed, In which the best moments of didactic gestures were identified. It is believed that the inclusive teaching gestures, as they are known, recognized and used in schools, can increase the possibility of knowledge being built through exchange of experiences and contributions shared approaching theoretical conceptions of lived realities, respecting the particularities of each individual space which is a heterogeneous classroom. For a better definition of didactic gesture was used as theoretical, conceptions of Sociolinguistics Interactionist, Rhetoric and Interactionism Sociodiscursive. Because this was a study in which no subjects involved in the interactions of everyday life, and situations in which the subjects can directly interfere in the actions of others, the method used is the phenomenological approach. This study is part of a further qualitative research since the results tend to offer contributions to the educational process. In the introduction to this thesis, are presented general information about the concern exists today, that education back to heterogeneous classrooms, as well as general explanations about the changing role of the teacher, in besides of the hypothesis that drove this research. There were scenes that were used to meet at the prospect of gestures by teaching presented herein. Finally, we present a synthesis of the results, establishing parallels between the hypothesis and the situation presented. In closing remarks, among other points, it is concluded that the teaching gestures, once known and recognized in the discursive action of the classroom, can make lessons more interactive and inclusive.